2020
DOI: 10.2174/2213235x07666190124120112
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Protocol for Extracting Aqueous Metabolites of High Lipid Sera

Abstract: Background: With the increasing focus of metabolomic methods on obesityrelated diseases, it is important to consider how sample handling may need to be adapted for the high compositions of lipids that can occur in such subjects. Introduction: High-lipid (cloudy, milky appearances; a.k.a. lipemic) biofluids are common in very high BMI subjects. Organic extractions of biofluids are useful for removing protein backgrounds, inactivating capsid viruses, and yielding relatively stable samples with excellent spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Although acetonitrile and water are miscible in all proportions, an interesting result connected to this work was the discovery of a liquid-liquid phase separation during the extraction of the majority of the samples [24], where high lipids likely constitute a third component and cause the observed phase separation. To reproducibly and reliably obtain aqueous metabolites, a slightly modified extraction protocol was implemented for the sera used in this study that includes a brief room-temperature step to break the liquid-liquid phase separation; this simple modification preserves the removal of proteins and may be of interest in metabolomics of obesity-related diseases [24]. [25]; a demographic statement is included in Methods.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Although acetonitrile and water are miscible in all proportions, an interesting result connected to this work was the discovery of a liquid-liquid phase separation during the extraction of the majority of the samples [24], where high lipids likely constitute a third component and cause the observed phase separation. To reproducibly and reliably obtain aqueous metabolites, a slightly modified extraction protocol was implemented for the sera used in this study that includes a brief room-temperature step to break the liquid-liquid phase separation; this simple modification preserves the removal of proteins and may be of interest in metabolomics of obesity-related diseases [24]. [25]; a demographic statement is included in Methods.…”
Section: Resultsmentioning
confidence: 80%
“…Samples were always on ice or refrigerated during handling, with one exception noted below. Each sample was re-vortexed for 30-45 s at 4 • C to ensure proper mixing and disruption of debris prior to centrifuging for 10 minutes at 4 • C and 10,600 rcf on a benchtop refrigerated centrifuge, after which it was often found that the supernatant consisted of two liquid phases, an intriguing behavior since these solvents are miscible in all proportions [24]. We have reported and resolved the phase separation separately [24].…”
Section: Organic Extraction Of Aqueous Metabolitesmentioning
confidence: 97%
See 1 more Smart Citation